DETECTION OFENTAMOEBAHISTOLYTICA IN STOOL SPECIMENS AMONG DIARRHEAL CHILDREN - H, Rafeef F.; Alsalim, H.A.A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to detect the spreading of E.histolytica among children with diarrhea, to achieve that,221 stool specimens were collected from diarrheal children of all ages and both gender, in Baghdad city at a period extended from early September 2019 to the end of February 2020. The collected specimens were examined directly by the light microscope for detecting the presence of E.histolytica. DNA was extracted from positive microscopically stool specimens, then examined by PCR to confirm the diagnosis of E. histolytica, by targeting the 18S ribosomal RNA(18S rRNA) gene. The result showed that 78 (35.3%) of diarrheal cases were caused by E. histolytica according to the microscopically direct smear method, while 143 (64.7%) were other diarrheal causes. The infection with E. histolytica rate in males (59%) was higher than in females (41%), however, this variation was not significant (P = 0.973). E. histolytica was considerably more prevalent in the age group<1-3 years (62.9%)and lower rate in the age group 10-12 years (3.8%). PCR examination results confirmed the presence of E. histolytica in 70 (89.7%) of 78 samples that were positive by microscopic examination which were 44 (62.8%) and 26 (37.2%) males and females respectively, this variation was significantly. Patients in the age group less than 1-3 years had the most infection with E. histolytica.